Differential Fibrotic Response of Muscle Fibroblasts, Myoblasts, and Myotubes to Cholic and Deoxycholic Acids - Valero-Breton, M; Cifuentes-Silva, E; Cabello-Verrugio, C; Tacchi, F; Orozco-Aguilar, J (Springer, 2023)
Fibrosis is a condition characterized by an increase in the components of the extracellular matrix (ECM). In skeletal muscle, the cells that participate in the synthesis of ECM are fibroblasts, myoblasts, and myotubes. These cells respond to soluble factors that increase ECM. Fibrosis is a phenomenon that develops in conditions of chronic inflammation, extensive lesions, or chronic diseases. A pathological condition with muscle weakness and increased bile acids (BA) in the blood is cholestatic chronic liver diseases (CCLD). Skeletal muscle expresses the membrane receptor for BA called TGR5. To date, muscle fibrosis in CCLD has not been evaluated. This study aims to assess whether BA can induce a fibrotic condition in muscle fibroblasts, myoblasts, and myotubes. The cells were incubated with deoxycholic (DCA) and cholic (CA) acids, and fibronectin protein levels were evaluated by Western blot. In muscle fibroblasts, both DCA and CA induced an increase in fibronectin protein levels. The same response was found in fibroblasts when activating TGR5 with the specific receptor agonist (INT-777). Interestingly, DCA reduced fibronectin protein levels in both myoblasts and myotubes, while CA did not show changes in fibronectin protein levels in myoblasts and myotubes. These results suggest that DCA and CA can induce a fibrotic phenotype in muscle-derived fibroblasts. On the other hand, DCA decreased the fibronectin in myoblasts and myotubes, whereas CA did not show any effect in these cell populations. Our results show that BA has different effects depending on the cell population to be analyzed. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.